Pharmacological and Non-Pharmacological Treatment in Non-Alcoholic Fatty Liver Disease - Perdana Aditya; Rinaldi A Lesmana (The Indonesian Society for Digestive Endoscopy, 2013)
Non-alcoholic fatty liver disease (NAFLD) is a spectrum of liver disease, from steatosis to liver cirrhosis in individual who does not consume alcohol in significant amount. The prevalence of NAFLD in Indonesia was estimated around 30%, this condition related to the increased incidence of metabolic disorders. Current understanding of NAFLD pathogenesis is the third-hit theory, in which insulin resistance resulting in free fatty acid accumulation that triggers inflammation causing fibrosis and hepatocyte death, and these conditions are not followed by adequate hepatocyte proliferation.Treatment of NAFLD requires both non-pharmacologic and pharmacologic interventions. Life style intervention includes restricting calories, low saturated fat and low sugar diet, and also physical activity. Bariatricsurgery remains controversial since in several study participants had experienced deterioration of disease. There are no definitive treatment for NAFLD currently. Treatment is aimed to improved insulin sensitivity, decreased oxidative stress and inflammation. Several agents use for treatment of NAFLD are insulin sensitizer (metformin and glitazones), statin, omega-3, vitamin E, ursodeoxycholic acid, orlistat, pentoxyphylline, and losartan.Keywords: NAFLD, treatment, pharmacologic, non-pharmacologic